Lesson Study Research and Practice in Mathematics Education Learning Together - Hart, Lynn C.; Alston, Alice S.; Murata, Aki.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Lesson Study has gained significant momentum around the globe in the mathematics education community in recent years. As a professional learning model based on collaboration, lesson study supports teacher learning of content, curriculum and student thinking as well as facilitating greater reflection and more focused conversations than is often realized with traditional types of professional development. While the body of knowledge about lesson study is growing, for many it remains somewhat elusive, often engaging in its implementation and research processes separately from one another while facing similar challenges and rewards. This volume attempts to unpack the complexity of lesson study and share current work and thinking outside of Japan. It brings together researchers, practitioners, and experts in lesson study to create a resource for much of the extant work being done.
Overview and History of Lesson Study -- Section I: Providing the necessary environment for Lesson Study -- Second II: Lesson Study as a Tool -- Section III- School-based Lesson Study -- Section IV - Preservice Lesson Study -- Section V - Walking the walk - University Faculty Engaged in Lesson Study -- Section VI - overall RESPONSE.
Keywords: Education; Mathematics; Education; Mathematics Education; Teaching and Teacher Education